Human Minds and Animal Stories How Narratives Make Us Care About Other Species - Małecki, Wojciech (Routledge Studies in World Literatures and the Environment, 2019)
The power of stories to raise our concern for animals has been postulated throughout history by countless scholars, activists, and writers, including such greats as Thomas Hardy and Leo Tolstoy. This is the first book to investigate that power and explain the psychological and cultural mechanisms behind it. It does so by presenting the results of an experimental project that involved thousands of participants, texts representing various genres and national literatures, and the cooperation of an internationally-acclaimed bestselling author. Combining psychological research with insights from animal studies, ecocriticism and other fields in the environmental humanities, the book not only provides evidence that animal stories can make us care for other species, but also shows that their effects are more complex and fascinating than we have ever thought. In this way, the book makes a groundbreaking contribution to the study of relations between literature and the nonhuman world as well as to the study of how literature changes our minds and society. "As witnessed by novels like Black Beauty and Uncle Tom's Cabin, a good story can move public opinion on contentious social issues. In Human Minds and Animal Stories a team of specialists in psychology, biology, and literature tells how they discovered the power of narratives to shift our views about the treatment of other species. Beautifully written and based on dozens of experiments with thousands of subjects, this book will appeal to animal advocates, researchers, and general readers looking for a compelling real-life detective story." - Hal Herzog, author of Some We Love, Some We Hate, Some We Eat : Why It's So Hard To Think Straight About Animals